Analisis Realisasi Pencapaian Target Penerimaan Pajak Daerah Terhadap PAD pada Badan Pendapatan Daerah Kabupaten Gorontalo - Lantowa, Felmi D; Ali, Yuwin; Iyonu, Mentari Ariesta; Wontami, Istiwati (CV. ULIL ALBAB CORP, 2024)
This study aims to determine the extent of realization and the contribution of regional tax revenue to the locally generated revenue (PAD) of Gorontalo Regency. The research adopts a quantitative descriptive method. Data collection was carried out using observation and documentation methods. The results of this study indicate that the contribution of regional taxes to PAD at the Regional Revenue Agency of Gorontalo Regency over the past five years falls within the medium category (20.00%-30%), with an average contribution of only 22.12%. The growth rate in 2018 was 23%, but it decreased to 13% in 2019, fell further to -1% in 2020, and dropped to -5% in 2021, before increasing by 12% in 2022. The average increase in the realization of regional tax revenue at the Regional Revenue Agency of Gorontalo Regency is 8.4%. This fluctuation is due to the inconsistency in achieving regional tax revenue targets, a lack of public compliance and awareness in fulfilling tax obligations, and the public’s inadequate perception of the function and benefits of taxes.